BR 287 Duplication Designed through the Methods of DNIT and MeDiNa (2020): Structural and Financial Analysis - Pascoal, Paula Taiane; Chiarello, Gabriéli Pires; Baroni, Magnos; Pereira, Deividi da Silva; Zucchi, Fernando Luiz (Anuário do Instituto de Geociências, 2022)
The paving field has experienced extensive changes due to the growth of traffic. In order to attend this evolution, it became necessary the implementation of a new methodoly for pavement designing that uses a mechanistic-empirical approach. This paper aims to compare, structurally and financially, three structures, one designed using the DNIT’s method and two through “Método de Dimensionamento Nacional – MeDiNa”. The three structures were analyzed concerning the behavior in relation to permanent deformation, fatigue life and regarding the necessary investment to pave one-kilometer duplication of an existent highway. Even though the two structures designed through MeDiNa were find to be more expensive than the one designed using DNITs precepts, when considering the cost related to the number of load requests supported by the pavement, structures designed through MeDiNa proved to be more reliable in face of layers damage and presented a good cost per supported requests.